Relative Risk of Fatal Injury in “High-Performance-Small-Motorcycle” Crashes in Malaysia - Pang, Toh Yen; Radin Sohadi, Radin Umar; Abdul Aziz, Azhar (Taylor & Francis, 2001)
This study present and analysis of injuries (severe and fatal) sustained by “High-Performance-Small-Motorcycle” users in Malaysia and establishes the relationship between fatality risk and human factors, exposure and vehicle factors resulting from motorcycle crashes. From the data gathered a statistical model based on logistic regression modeling technique has been developed. Five variables found to have a significant influence on fatality risk (p<0.05) were age, location sites, engine capacity, object/vehicle struck and collision types.